Gestión administrativa y su relación con la calidad de los procesos administrativos de la unidad de gestión administrativa de gestión educativa local de Ucayali-Contamana año 2019 - Torres Bartra, Anderson (2022)
The objective of this study was to determine the relationship between administrative management and the quality of the administrative processes of the Local Educational Management Unit of Ucayali-Contamana, year 2019, as it was a descriptive correlational research and non-experimental design, since it was took 50 workers as the population and sample, to whom a survey and a questionnaire were applied as an instrument respectively, obtaining as results that the administrative management of the UGEL of Ucayali-Contamana is deficient (37%), this due to the fact that the workers They consider that the director almost never has the capacity to make decisions regarding the objectives, also, they pointed out that he almost never efficiently fulfills his responsibilities. On the other hand, At the same time, it is possible to determine that the quality of the administrative processes in said institution is bad (40%), this due to the fact that the procedure to request the rectification of evaluation records and official payrolls is regular, however, the procedure for the approval of supplementary credit is bad as well as the procedure for granting the UGEL pass presents problems and finally the administrative procedure followed in compliance with the judicial sentence is bad. Finally, it was concluded that administrative management is significantly related to the quality of the administrative processes of the UGEL of Ucayali-Contamana, in 2019; This has been contrasted with the bilateral significance of 0.000 and a positive and considerable correlation coefficient (Spearman's Rho) of 0.813.